2015
DOI: 10.1007/s40195-015-0265-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Magnetic Properties Modulated by Adsorption of 3d Transition Metal Atoms in Monolayer and Bilayer MoS2 Sheets

Abstract: The adsorption effects of 3d transitional metal (TM) adatoms on electronic and magnetic properties of monolayer and bilayer MoS 2 sheets have been investigated by using first-principle calculations based on the density functional theory. The calculated results suggest that both monolayer and bilayer MoS 2 sheets have power abilities of absorbing 3d TM atoms. The interlayer adsorption of bilayer MoS 2 is relatively more stable than the surface adsorption of monolayer MoS 2 . The 3d TM adatoms and the neighborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…As we known, introducing of transition metal (TM) atoms in 2D materials has been demonstrated to be the most conventional and effective method to modify the magnetism. [27][28][29][30][31][32][33][34][35] Furthermore, TM-doped 2D materials have been synthesized by pulsed laser deposition 36 and electron beam irradiation. [37][38][39][40] Some theoretical investigations have revealed that a magnetic state can be achieved by TMdoping.…”
Section: Introductionmentioning
confidence: 99%
“…As we known, introducing of transition metal (TM) atoms in 2D materials has been demonstrated to be the most conventional and effective method to modify the magnetism. [27][28][29][30][31][32][33][34][35] Furthermore, TM-doped 2D materials have been synthesized by pulsed laser deposition 36 and electron beam irradiation. [37][38][39][40] Some theoretical investigations have revealed that a magnetic state can be achieved by TMdoping.…”
Section: Introductionmentioning
confidence: 99%
“…For the Cr and Fe d-type alternatively codoped systems, we considered two congurations, named FeFeCrCrchain-MoS 2 and FeCrFeCr-chain-MoS 2 . To estimate the stability of the four d-type doping congurations, the average binding energy (E b ) was calculated as Previous studies have shown that monolayer MoS 2 appears to be magnetic aer being doped with TM atoms, 29,30 thus we should rstly consider the magnetic exchange coupling between Cr and Fe, which determines the magnetic order of Cr/Fe-chain-MoS 2 . To ascertain the stable magnetic state, we calculate the energy of the antiferromagnetic and ferromagnetic states for all systems, and dene dE as the energy difference between the ferromagnetic and antiferromagnetic states, with the results being listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The pristine MoS 2 analogous to graphene is a nonmagnetic material. To promote its applications in spintronics, methods including cutting the material into zigzag MoS 2 nanoribbons, 28 transitional metal (TM) adsorption, 29,30 and TM doping [31][32][33][34] were used. Among them, TM substitutional doping is one of the most simple and effective techniques to modulate the electronic and magnetic properties of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The Brillouin-zone integration was sampled using a 5 × 5 × 1 k-mesh according to the Monkhorst-Pack scheme for structure relaxation and a 7 × 7 × 1 k-mesh for single-point calculation. The structure was fully relaxed for an energy convergence of 1.0 × 10 −5 eV and force convergence of 0.01 eV Å −1 [39,40]. The in-plane biaxial strain was imposed by varying the lattice constant a and is computed as ε = (a − a 0 ) /a 0 , where a 0 and a are the lattice constants of the monolayer MoS 2 in its equilibrium and strained states, respectively.…”
Section: Calculation Detailsmentioning
confidence: 99%